HUMAN RESOURCE MANAGEMENT AND DEMOCRATIC LEADERSHIP STYLE ON EMPLOYEE PERFORMANCE IN THE DEPARTMENT OF AGRICULTURE AND FOOD SECURITY, ROTE NDAO REGENCY - Defrid Chris Yermi Nesimnasi; Frans Gana; Melkisedek N. B. C. Neolaka (RADJA PUBLIKA, 2026)
This study aims to examine the effect of human resource management (HRM) and democratic leadership style on employee performance at the Agriculture and Food Security Office of Rote Ndao Regency. A quantitative research approach was employed, with a population of 124 employees. Using a total sampling technique, 123 respondents were included in the study. Data were collected through structured questionnaires measuring employee performance, human resource management practices, and democratic leadership style. The data were analyzed using multiple linear regression techniques. The results indicate that both human resource management and democratic leadership style have a positive and significant effect on employee performance. Partial testing (t-test) shows that each independent variable significantly influences employee performance at a significance level below 0.05. Furthermore, the simultaneous test (F-test) confirms that human resource management and democratic leadership style jointly affect employee performance. These findings highlight the critical role of effective human resource management and participatory leadership in enhancing employee performance. Therefore, organizational management is encouraged to strengthen human resource development and adopt democratic leadership practices to achieve optimal organizational performance.